Influence of electronic vs nuclear energy loss in radiation damage of Ti3SiC2. (December 2018) - Hanson, William A.; Patel, Maulik K.; Crespillo, Miguel L.; Zhang, Yanwen; Weber, William J.
Abstract: The thermal conductivity and stability of MAX phases has led to irradiation studies of these materials for their possible application in the hostile environments of high temperature and radiation. Numerous neutron and ion irradiation studies have been conducted that demonstrate that radiation induced modifications consists of lattice strain and increased formation of TiC. Ion beams have been used to simulate damage created by neutrons; however, what is not clear is the effect of varying electronic to nuclear energy loss on the damage evolution within this material. In the present work, changes in c/a within Ti3 SiC2 are monitored as a function of energy deposition at constant damage dose following high fluence 9 M e V Ti ion irradiations at room temperature. The results reveal that there is an apparent threshold in the electronic energy loss, above which the c/a ratio and TiC concentration starts to increase with increasing electronic energy loss. Interestingly, this change is independent of the damage dose in displacements per atom. This suggests that inelastic energy dissipation is of paramount importance when selecting ions for simulating damage by energetic neutrons. Graphical abstract: Image 1